2001
DOI: 10.1007/s002470100456
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing dysfunction in infants less than 1 year of age

Abstract: Careful evaluation of swallowing during an UGI can identify swallowing dysfunction in full-term infants who have respiratory problems, as well as in infants with an abnormality that predisposes the patient to aspiration. Episodes of tracheal aspiration may be fleeting and overlooked if swallowing is not assessed carefully. An MBSS can confirm the observation of swallowing dysfunction found during an UGI and assist in planning appropriate dietary therapy that minimizes the likelihood of tracheal aspiration duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
5
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 0 publications
4
76
5
5
Order By: Relevance
“…It has also been suggested that cough is a less reliable indicator of aspiration in a younger age group, due to disruptions in postnatal maturation of airway clearance mechanisms or desensitisation secondary to repeated aspiration [11,27]. In particular, apnoea has been noted to be indicative of aspiration in infants, with cessation of respiration, closure of the airway and multiple swallows until clearance of the aspirated substance has occurred [11,28]. The current authors found that infants demonstrated stridor, apnoea/desaturations and wet breathing significantly more frequently during feeds than the older group, but none of these signs were significantly associated with OPA.…”
Section: Influence Of Age and Neurological Statusmentioning
confidence: 99%
“…It has also been suggested that cough is a less reliable indicator of aspiration in a younger age group, due to disruptions in postnatal maturation of airway clearance mechanisms or desensitisation secondary to repeated aspiration [11,27]. In particular, apnoea has been noted to be indicative of aspiration in infants, with cessation of respiration, closure of the airway and multiple swallows until clearance of the aspirated substance has occurred [11,28]. The current authors found that infants demonstrated stridor, apnoea/desaturations and wet breathing significantly more frequently during feeds than the older group, but none of these signs were significantly associated with OPA.…”
Section: Influence Of Age and Neurological Statusmentioning
confidence: 99%
“…Videofluoroscopic swallow study (VFSS) is the gold-standard radiographic test for evaluating swallowing, 9 and VFSS abnormalities are common among infants clinically thought to have difficulty swallowing. [10][11][12][13] Which infant characteristics predict VFSS abnormalities and whether interventions designed to protect the airway are efficacious remain unclear. An observational study in infants with neurologic impairment did not find a decrease in respiratory admissions after fundoplication.…”
mentioning
confidence: 99%
“…Children with respiratory problems may present swallowing alterations, which can be observed in videofluoroscopic evaluation (22,(24)(25)(26) . According to some authors, swallowing disorders are frequently observed in infants with history of bronchitis and/or recurrent pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Swallowing disorders with aspiration are a common cause of difficulties related to feeding in infancy (12) . Studies have showed that videofluoroscopy is a method able to detect aspiration, silent or not, and to appropriately identify the swallowing alterations, which allow therapeutic planning and the establishment of compensatory mechanisms (12,22,23) . Abnormal videofluoroscopy results in newborns include nasopharyngeal reflux, laryngeal penetration and aspiration, with a high incidence of silent aspiration.…”
Section: Introductionmentioning
confidence: 99%